PENANAMAN VALUE BERAKHLAK BAGI ASN GURU - Resekiani Mas Bakar; St Hadjar Nurul Istiqamah; Elshafa Salsabil Anwar; Muh Irsyad (Jurnal Kebajikan: Pengabdian Kepada Masyarakat, 2023)
The work behavior of ASN teachers in everyday life is based on the value of BerAKHLAK. The implementation of BerAKHLAK values cannot be achieved if civil servants do not know and understand these values. ASN Teacher service activities aim to provide knowledge related to the value of BerAKHLAK by exploring self-awareness and application of these values in the teacher's daily work activities. The approach method carried out in instilling BerAKHLAK values uses coaching groups. The participants of the activity were 31 ASN MAN 2 Polewali Mandar teachers. The activity of providing BerAKHLAK material and coaching group was carried out for 120 minutes (2 hours). ASN teachers show high involvement in participating in activities. The evaluation results show that training activities are considered useful and relevant in instilling BerAKHLAK values for ASN teachers.